(untitled) (Studia austriaca, 2020)
Musicologists would consider Gustav Mahler’s symphonies heterophonic, while literary scholars might read them as modern narratives that invite a myriad of interpretations. This road into the open is reflected in Arthur Schnitzler’s 1908 novel Der Weg ins Freie. The protagonist Georg von Wergenthin is a Mahlerian figure, enamored of Vienna but also in search of a way out. This paper is a comparative study of Mahler’s music in its dialogue with literature – from Dante and Goethe to D’Annunzio and Hofmannsthal – as well as their shared characteristics that come to shape fin-de-siècle Viennese modernity.